Peran Dinas Perhubungan dalam Peningkatan Kedisiplinan Berkendara di Kabupaten Bima - Nurhadi Nurhadi; Rahimudin Rahimudin (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
Bima Regency public awareness regarding driving discipline is still low, this is due to the high number of accidents caused by several factors including underage children driving, drivers not wearing helmets, reckless driving, and running red lights, of course this requires a role. important for the Transportation Service, especially the special division for traffic. This research aims to determine the role of the Transportation Department in improving driving discipline in Bima Regency and the factors that influence driving discipline in Bima Regency.The research is a qualitative descriptive study using primary data and secondary data. Primary data in this research was obtained from interviews conducted in the traffic sector and direct observation at the Bima Regency Transportation Service, while secondary data in this research were laws, articles, journals, previous research and so on, which became supporting data for the research after primary data.The results of the research show that in carrying out the duties of the transportation service in improving driving discipline in Bima district, efforts have been made and implementing policies to increase driving awareness, including carrying out patrols, raids, road security, outreach to the community and schools. The main factor that influences driving discipline in Bima Regency is knowledge of traffic rules and coupled with very hot weather conditions which make drivers less focused and aware of the road and traffic rules.